Analysis of influencing factors of early neurological improvement after intravenous rt-PA thrombolysis in acute anterior circulation ischemic stroke - Xiufu, Zhang; Ruipeng, Liang; Jun, Zhou; Yonglong, Li; Yulin, Wang; Jian, Zeng; Xianglin, Chen; Lan, Shen; Zuowen, Zhang (Frontiers in Neurology, 2022)
It has been widely reported that Early neurological improvement (ENI) after rt-PA intravenous thrombolysis contributes to a good long-term prognosis in patients experiencing acute ischemic stroke (AIS). However, which clinical factors influence after intravenous administration of recombinant tissue-type plasminogen activator (IV-rt PA) in AIS patients ENI is still unclear. This study aimed to investigate the clinical factors affecting ENI in patients with acute anterior circulation ischemic stroke after intravenous thrombolysis with rt-PA. This retrospective study shows that in patients with acute precirculation ischemic stroke who receive rt-PA intravenous thrombolysis, diabetes mellitus (hyperglycemic levels) is a clinical risk factor for ENI after thrombolysis.